ANALISIS SEMBURAN RADIO MATAHARI TIPE II SEBAGAI PREKURSOR KEMUNGKINAN TERJADINYA BADAI MAGNET BUMI - - Suratno; Santi Sulistiani (Jurnal Sains Dirgantara, 2010)
The solar flare, type II solar radio bursts and Coronal Mass Ejection (CME) are the serial phenomena of the sun which have a closed association. The occurence of type II solar radio bursts is triggered by passing of shock wave and is showing the ejection of plasma and magnetic fields. The shock wave or CME travelling toward the earth’s upper atmosphere can lead to the occurence of geomagnetic storm. Since the bursts propagation mechanism is by means of electromagnetic radiation and reaches the earth within 8 minutes, the shock wave or CME will reach the earth within 40 to 80 hours or even it is exceeding 5 days, hence, the type II bursts can be used as an early indicator information of the possibility incident of the geomagnetic storm. This investigation is carried out by analysing the travel time of shock wave which is determined from the dynamic spectra of type II solar radio bursts and the onset time of the geomagnetic storm. This travel time then is compared to the difference between start time of type II bursts and the instant of minimum Dst (Disturbance storm time). This analysis is supported by the data of active region position on the solar disk as a source of bursts and the direction of interplanetary magnetic field. Keyword: Solar flare, Type II solar radio bursts, Geomagnetic storm